الرقابة على السلطة التنظيمية في النظام الدستوري الجزائري - أيوب مسعودي (جامعة محمد بوضياف المسيلة, 2025)
Regulations are a means of exercising the regulatory authority stipulated in Article 141 of the 2020 Constitutional Amendment, which reflects the broad and undefined scope of the regulation, especially the independent regulations issued by the President of the Republic. This forced the constitutional founder to establish oversight of the regulatory authority through constitutional and judicial oversight, via independent constitutional institutions that exercise the oversight process assigned to them according to specific mechanisms, controls, and procedures, embodying the principle of legitimacy and thus the rule of law.
Keywords: Regulations- Constitutional Court- Constitutional oversight- Amendment